Life History Method to Study Policy Changes and its Impact on Teachers’ lives: Experiences, Dilemmas and Reflections - Kalra, Parul (Voices of Teachers and Teacher Educators, 2021)
This paper is based on the methodology used for the doctoral research that is, life history method to study policy changes and its impact on teachers’ lives. The paper sketches out the process of data collection from the beginning to end. It throws light on the participants’ views that is, teachers’ views on the methodology used by the researcher. In the last two sections, the paper delineates dilemmas faced by the researcher and reflection on methodology and its dimensions which helped the researcher to navigate through teachers’ lives to study the educational policy changes.